2021
DOI: 10.1080/15348431.2021.1949994
|View full text |Cite
|
Sign up to set email alerts
|

What Helps Students Get Help?: An Exploratory Analysis of Factors that Shape Undocumented College Students’ Use of Academic Support Services

Abstract: Academic support services are an important institutional resource that can support student success and retention. However, little research has examined undocumented students' resource uptake, aside from demonstrating that exclusionary policies and experiences reduce undocumented students' access to and use of institutional resources. In this article, we use regression analysis to identify what factors may contribute to undocumented students' use of academic support services. Drawing on a survey of 1,277 undocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In line with this work, a recent large-scale survey of over 96,000 college students found that severity of psychological problems was the most robust predictor of students' use of low-cost or no-cost university-based mental health services (Pilar et al, 2020). Although undocumented students report multiple psychological concerns that merit professional attention, including high levels of depression, anxiety, and stress Hagan et al, 2021;Ro et al, 2021;Suárez-Orozco & Lo ´pez Hernández, 2020), whether greater symptom severity relates to a higher likelihood of seeking mental health support among undocumented students is unknown.…”
Section: Individual-level Factorsmentioning
confidence: 79%
See 2 more Smart Citations
“…In line with this work, a recent large-scale survey of over 96,000 college students found that severity of psychological problems was the most robust predictor of students' use of low-cost or no-cost university-based mental health services (Pilar et al, 2020). Although undocumented students report multiple psychological concerns that merit professional attention, including high levels of depression, anxiety, and stress Hagan et al, 2021;Ro et al, 2021;Suárez-Orozco & Lo ´pez Hernández, 2020), whether greater symptom severity relates to a higher likelihood of seeking mental health support among undocumented students is unknown.…”
Section: Individual-level Factorsmentioning
confidence: 79%
“…These results may reflect the importance of having a positive attitude toward seeking formal support in general, as has been found in other studies of mental health service use among young people (Gulliver et al, 2010). It is also possible that students who access general student services on campus may have a greater capacity to seek help for their concerns overall, more extensive social networks, and/or more awareness of university services that could benefit them (e.g., Sarabia et al, 2021). Further, undocumented student services foster feelings of belonging and safety among undocumented students (Cisneros & Valdivia, 2020; Enriquez et al, 2019), possibly facilitating their comfort with accessing on-campus mental health services and/or supporting their attempts to acquire services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond in‐class instruction, many summer bridge programs offer individual or group tutoring sessions. Tutors can often provide what course instructors are not able to offer based on class size constraints: the ability to answer individual questions, correct student mistakes, and offer depth of inquiry (Dioso‐Henson, 2012; Sarabia et al., 2021). Hodges and White's (2001) study also showed that students often underestimate how much help they may need in introductory courses; as such, institutions often provide tutoring during summer bridge programs even when students do not request it themselves.…”
Section: Summer Bridge Programs: An Overviewmentioning
confidence: 99%